2021
DOI: 10.21037/atm-20-3166
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of RNAi therapeutic miR-26a-5p targeting cMet and immunotherapy against EGFR in endometrial cancer treatment

Abstract: Background: Precise prediction of drug combination targeting tumor cells effectively is a crucial challenge for tumor therapy, especially for endometrial cancer (EC). Considering the resistance, crosstalk that occurs between the receptor tyrosine kinase mesenchymal-epithelial transition factor (cMet) and epidermal growth factor receptor (EGFR), and their indispensable influence on the occurrence of EC, this study aimed to explore a novel therapeutic approach for EC treatment through blocking cMet and EGFR simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Our recent study (under review) found that up to 7 miRNAs (miR-519a-5p, miR-199b-3p, miR-199a-3p, miR-148a-3p, miR-26a-5p, miR-512-3p, and miR-143-3p) identified in placental EVs inhibited ovarian or endometrial cancer cell proliferation and migration, and promoted cancer cell death. Interestingly, most of these miRNAs have been reported to be downregulated in ovarian ( 66–70 ) and endometrial cancer tissues or cell lines ( 71 , 72 ). Recently, we found that treating ovarian cancer cells with placental EVs isolated from first trimester placentae significantly reduced ovarian cancer cell proliferation due to a delay in cell cycle progression ( 73 ).…”
Section: Extracellular Vesicles the Placenta And Tumorsmentioning
confidence: 99%
“…Our recent study (under review) found that up to 7 miRNAs (miR-519a-5p, miR-199b-3p, miR-199a-3p, miR-148a-3p, miR-26a-5p, miR-512-3p, and miR-143-3p) identified in placental EVs inhibited ovarian or endometrial cancer cell proliferation and migration, and promoted cancer cell death. Interestingly, most of these miRNAs have been reported to be downregulated in ovarian ( 66–70 ) and endometrial cancer tissues or cell lines ( 71 , 72 ). Recently, we found that treating ovarian cancer cells with placental EVs isolated from first trimester placentae significantly reduced ovarian cancer cell proliferation due to a delay in cell cycle progression ( 73 ).…”
Section: Extracellular Vesicles the Placenta And Tumorsmentioning
confidence: 99%
“…These miRNAs are vital for orchestrating immune control within tumor infiltrations (15). One such miRNA, miR-26a-5p, was found to target tumor cells and inhibit the progression of various carcinomas, including renal cell carcinoma, NSCLC, as well as endometrial cancer (16)(17)(18). Yet, the precise regulatory mechanism of miR-26a-5p in tumor-infiltrating T lymphocytes remains unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-26a-5p promoted tumor progression by suppressing activation of PTEN signaling in the non-small cell lung cancer [ 10 ]. The expression of miR-26a-5p was significantly reduced in endometrial cancer and cell lines, and overexpression of miR-26a-5p enhanced the inhibitory effect of cetuximab by regulating cMet/HGF pathway in vivo and in vitro [ 11 ]. The miR-26a-5p/ARPP19 axis modulated nasopharyngeal carcinoma progression by sponging lncRNA SNHG6 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%